Ontogeny of the flowers in Paulownia tomentosa - a contribution to the recognition of the resurrected monogeneric family Paulowniaceae - Erbar, Claudia; Gülden, Christoph (Flora, 2011)
Disintegration of the Scrophulariaceae due to molecular data resulted in re-circumscriptions, resurrection and new descriptions of families to encompass the monophyletic lineages. In some of these families floral morphological/ontogenetic data, however, are largely missing, as, for example, in Paulowniaceae. This study reveals a set of distinctive features that were up to now unknown in Paulowniaceae: In the lateral flowers of the inflorescence, initiation sequence in calyx and corolla is unidirectional in identical direction, starting at the adaxial side; the formation of sympetaly is late but ledges connecting the separate petals arise relatively early. Of importance are particularly the occurrence of: crescent-shaped archespore and pollen sacs with a pollen sac placentoid, secretory tapetum, a several cell layers thick endothecium, endothecium-like cells situated all over the tissue of the theca except in the placentoid, undivided placenta originating in each locule on the septum only, a tubular stigma with papillae inside a dilated chamber (in this character Paulownia differs from all other members of the Lamiales-clade!), nectary in the basal part of the superior ovary, and small, winged seeds whose testa possesses protrusions that laterally expand into several sinuate wings, gradually increasing in extension towards the two margins. When continuing to resolve and stabilize the relationships of clades, it should be one of the goals to find new, visually perceptible data that enable easy identification of clades. For Paulowniaceae, these distinctive characters are the peculiar shape of the multi-winged seeds with their lateral wings gradually increasing in size and the tubular stigma with papillae inside a dilated chamber.
Available online 15 December 2010
Gesehen am 29.4.2022